Dynamic electrical failure of carbon nanotube ribbons. (15th January 2023) - Bai, Yunxiang; Zhu, Mingquan; Wang, Shijun; Liu, Luqi; Zhang, Zhong
Abstract: Emerging carbon nanotube (CNT)-based cutting-edge applications such as fast-response artificial muscle, fast-charging energy storage system, lightning strike protector, etc. Call for the study of dynamic electrical failure (DEF) of CNTs. In addition, the reported ampacities of CNTs were tested under different electrical signal applying conditions ( e.g. the duration of testing), which led to the direct comparison of them may be virtually invalid. Here, the DEF behavior and mechanism of carbon nanotube (CNT) ribbons was studied by experiments and theoretical calculations as well. The considerable impact of electrical stress rates (ESRs) is demonstrated. Electrical failure resistance (EFR) of CNT ribbons increases with increasing ESR (from 0.5 V/s to 200 V/s), both in air and vacuum. EFR in vacuum is generally higher than that in air. This discrepancy attenuates significantly at high ESR regime due to the vacuumizing oxygen failure (VOF) mechanism (thermal oxidation is largely suppressed) in air. The DEF behavior is outlined by a theoretical model and a cube root relationship between EFR and ESR is obtained. We obtain that the way to apply electrical signal has a significant effect on the testing ampacity result and the establishment of a uniform standard of ampacity testing method is highly recommended. Graphical abstract: We studied the DEB of carbon nanotube (CNT) ribbons. The considerable impact of electrical stress rates (ESRs) is demonstrated. Electro-failure resistance (EFR) of CNT ribbons increases with increasing ESR (from 0.5 V/s to 200 V/s), both in air and vacuum. EFR in vacuum is generally higher than that in air. This discrepancy attenuates significantly at high ESR regime since thermal oxidation is largely suppressed in air. The dynamic electro-failure mechanism is outlined by a theoretical model. A cube root relationship between EFR and ESR is obtained. We obtain that the way to apply electrical signal has a significant effect on the testing ampacity result and the establishment of a uniform standard of ampacity testing method is highly recommended. Image 1